ANALISIS PENGARUH KONEKSI POLITIK, PERGANTIAN DIREKSI, DAN BOARD GENDER DIVERSITY TERHADAP MANAJEMEN SKANDAL - Devia Rizky Amelia (2021)
This study aims to examine the effect of political connections on the board of commissioners and board of directors, the turnover of members of the board of commissioners and board of directors, and board gender diversity on scandal management. The control variables in this study are company size, leverage, book-to-market, and profitability. The sample used in this study are Kompas 100 Index companies and companies that representing 9 sectors for the period 2015 to 2019 which is listed on the Indonesia Stock Exchange (IDX). The sample selection technique in this study used purposive sampling by setting certain criteria and collecting 104 company samples. Hypothesis testing in this study uses Multinomial Logit Regression with the STATA version 12 program. Scandal management in this study uses two categories, namely the Corruption Scandal (MSK) and the Legal Scandal (MSH). This study showed that political connections on the board of commissioners, changes in the board of directors and commissioners, and board gender diversity do not affect the occurrence of management of corruption scandals or law. In addition, this study showed that political connections on the board of directors and the presence of board gender diversity have a significant effect on the management of corruption scandals, but have no effect on management of legal scandals.